Implementing healthcare interoperability utilizing SOA and data interchange agent. Issue 3 (September 2015) - Batra, Usha; Sachdeva, Shelly; Mukherjee, Saurabh
Abstract: Integration of IT with healthcare system requires interoperability that may lead to open connectivity at all levels (i.e. inPatient and outPatient care). This could be achieved by introducing interoperability among various healthcare service providers which is important for ensuring that patient information is available anytime and right at the point of care, eliminating unnecessary delay in treatment, avoiding replication of test reports, improving more informed decisions and hence leading to improved quality of care. So, there is a need of an integrated healthcare system that handles the exchange of medical data coming from different healthcare service providers. With this intent, in this paper we present an interoperable healthcare information system that considers data integration and interoperability of patients׳ information available with various healthcare service providers in a heterogeneous environment. The challenge lies in availability of wide variety of standards and illustration of same medical record in different structures. This could be ruled out by introducing the concept of web services technology to solve the interoperability problems in the healthcare domain. Considering the distributed and heterogeneous environment of healthcare domain, there are two ways for exchanging healthcare information. One is that each hospital/clinical system should use/follow the same standard, and the other is utilizing service oriented architecture. Standardizing the access to data through the most promising solution of web services, rather than standardizing the electronic health record will help to overcome the integration problems with improved performance among different standards in medical information systems. The proposed system utilizes concept of web services with a compliance of Service Oriented Architecture (SOA) and data interchange agent that converts medical data coming from wide-ranging healthcare service providers into a standard data interchange format. Here, two xml databases are used like, service provider database and patient profile database. These two databases may be in various system formats. So, there is a need to convert it into standard format before it is stored in the data repository (database). Whenever a patient gets treatment from the service provider, both databases are updated with respect to relevant information and at the same time, the information presented in both databases is also extracted. Whole process is implemented using the web services and the message is transferred using the SOAP protocol. Furthermore, the accessing of service customer or service provider details can be done only if the authentication is given from the security agent. Finally, the accessing of information from database is achieved efficiently with the help of proposed searching algorithm that reduces almost 33% time needed to retrieve the desired data from the database. This research will benefit the prevalent electronic health record standards such as Health Level 7 (HL7) [1], openEHR [28], CEN/ISO 13606 [29] working towards semantic interoperability for efficient searching of patient records and hence improved performance.